A Bioprinting Process Supplemented with In Situ Electrical Stimulation Directly Induces Significant Myotube Formation and Myogenesis. (7th August 2021) - Kim, WonJin; Lee, Hyeongjin; Lee, Chang Kyu; Kyung, Jae Won; An, Seong Bae; Han, In‐Bo; Kim, Geun Hyung
Abstract: Electric field stimulation has supported biophysical and biological cues for tissue regeneration approaches to affect cell morphology, alignment, and even cellular phenotypes types. Here, an innovative bioprinting approach supported by in situ electrical stiumlation (E‐printing) is used to fabricate a bioengineered skeletal muscle construct composed of human adipose stem cells and methacrylated decellularized extracellular matrix (dECM‐Ma) derived from porcine muscle. To obtain highly ordered myofiber‐like structures, various parameters of the printing process are optimized. The E‐printed structure exhibits higher cell viability and fully aligned cytoskeleton than the conventionally printed cell‐bearing structures, due to activation of voltage‐gated ion channels that affect various signaling pathways. When using the E‐printed structure, expression of myogenesis‐related genes is upregulated by 1.9–2.5‐fold higher than when using a dECM‐Ma structure produced without electrical stimulation. Furthermore, when implanted into a rat model of volumetric muscle loss, the structure yields outstanding myogenesis relative to the conventionally bioprinted structure. Abstract : Using an innovative bioprinting approach supported by in situ electrical stimulation, a bioengineered skeletal muscle construct composed of human adipose stem cells and a methacrylated decellularized extracellular matrix derived from porcine muscle is fabricated. When implanted into a rat model of volumetric muscle loss, the structure yields outstanding myogenesis relative to the conventionally bioprinted structure.